NRG1, PIP4K2A, and HTR2C as Potential Candidate Biomarker Genes for Several Clinical Subphenotypes of Depression and Bipolar Disorder; Frontiers in Genetics; Vol. 11 - Levchenko A. S. Anastasiya Sergeevna; Vyalova N. M. Nataljya Mikhaylovna; Nurgaliev T.; Pozhidaev I. V.; Simutkin G. G. German Gennadjevich; Bokhan N.; Ivanova S. A. Svetlana Aleksandrovna (2020, 2020)
Title screen